An approach for low energy mosque building design in hot arid climate: a case for Saudi Arabia - Alabdullatief, Aasem (2020)
The number of mosque buildings is continuously increasing with the Muslim population, which is fast growing around the world. In particular, the demand of new mosque buildings is high in the urban areas, due to increasing urban population growth in many parts of Muslims countries, as a result of economic growth and political instabilities in some parts of the Muslims world. Mosques are becoming more overcrowded and as a result a number of researches have been conducted to address the issue of thermal comfort of mosques’ users and efficient cooling solutions. The motivator of this research is the lack of researches in sustainable mosques, where the current condition of mosque buildings is not satisfying.